2004
DOI: 10.1086/424537
|View full text |Cite
|
Sign up to set email alerts
|

Optical Monitoring of Three Gamma-Ray-loud BL Lacertae Objects in 1999-2002

Abstract: We present the results of optical photometric (BVRI ) monitoring of three gamma-ray-loud BL Lac objects (3C 66A, PKS 0735+178, and BL Lacertae) in 1999-2002. During our observations, these objects showed significant rapid variations: 3C 66A and PKS 0735+178 exhibit short-timescale ($1 hr) variability in the B band, and BL Lac exhibits intraday variability in B and V. We find that there is a strong correlation between brightness and color for 3C 66A and BL Lac. We have analyzed the relationship between optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 56 publications
4
15
1
Order By: Relevance
“…A bluer-when-brighter behaviour was also detected by other authors in datasets more or less extended in time (e.g. Zhang et al 2004;Stalin et al 2006;Gu et al 2006).…”
Section: Introductionsupporting
confidence: 78%
“…A bluer-when-brighter behaviour was also detected by other authors in datasets more or less extended in time (e.g. Zhang et al 2004;Stalin et al 2006;Gu et al 2006).…”
Section: Introductionsupporting
confidence: 78%
“…The largest optical variations registered are on the order of 3-4 mag (Pollock et al 1979;Fan et al 1997) at long (years) ranges. Some intra-day (IDV) and inter-day variations until 0.5 mag were reported in the optical history of this blazar (Xie et al 1992;Fan et al 1997;Massaro et al 1995;Zhang et al 2004). Over the period 1995-1997, the optical IDV and microvariations were rare and with a small amplitude (Bai et al 1999), while no clear evidence was found in more recent observations (Sagar et al 2004).…”
Section: Optical Properties Of Pks 0735+178mentioning
confidence: 94%
“…Optical IDV up to 0.5 mag has been reported in the source on some occasions (e.g. Xie et al 1992;Massaro et al 1995;Fan et al 1997b;Zhang et al 2004). PKS 0735+178 has shown a high degree of optical and near-infrared polarizations which varies from 1% to 30% (e.g.…”
Section: Idv and Short-term Variability Of Individual Blazarsmentioning
confidence: 95%